Somiglianze di famiglie — tra Wittgenstein e la “scuola schellinghiana” - Di Maio, Francesco (Aesthetica Preprint, 2023)
Ludwig Wittgenstein made extensive and explicit use of the concept of ‘Family resemblance’, attributing a technical meaning to this expression. This contribution emphasises an ambiguity in the Viennese philosopher regarding this lemma (§2), sometimes an extension of the concept of γένος, other times an instrument for connecting irreducible multiplicities (§3). Therefore, in order to find a structural reason for this ambivalence, this text returns to Arthur Schopenhauer who accused the so-called “Schellingian school” of overusing this concept (§4). Individuating the referent of the vague formula in Henrik Steffens (§5), this paper finally attempts to point out an actual “family resemblance” between Wittgenstein and F.W.J. Schelling. Indeed, by reading the one with the other, the last part of this contribution (§6) shows how the ambiguity of the former’s use of Familienähnlichkeit can be traced back to the “criticist” and “dogmatist” positions outlined in the latter’s Philosophical Letters.